Mathematical Modeling of a Flat Plate Solar Collector with Eutectic Salts as Phase Change Material - Isamotu, O. F.; Musa, N. A.; Okegbile, O. J.; Oriaifo, M. A.; Bakare, A. O. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2020)
Solar energy is the most promising heat source for meeting energy demand without having negative impact on the environment. Solar energy is, however, intermittent in nature and time dependent energy source. In order to mitigate the intermittent supply of solar energy for water heating, the use of phase change material (PCM) comes into play. The PCM acts as a heat source for the solar heating system when the intensity of the solar radiation is low or no longer active. Knowledge about the thermal effectiveness of solar collector with PCM is paramount. So, this study developed a mathematical model to evaluate the thermal behavior of a flat plate solar collector integrated with a phase change material (PCM). This mathematical model developed for the flat-plate with PCM was based upon the conservation and heat transfer equations and used to predict the thermal behavior of integrated phase change material in solar collector during thermal storage. The energy balance equations for the flat-plate heating components of the collector and PCM were formulated numerically. The model was used to investigate the effect of inlet water temperature, water mass flow rate, outlet water temperature and the melt fraction during charging and discharging modes at each of the respective nodes. A comparison was made with a collector with and without PCM. The results show that charging and discharging processes of PCM have multiple stages. The addition of PCM in the first stage causes a decrease in temperature during charging and an increase during discharging. The highest water temperatures reached for the collector without and with a phase change material were approximately 51 and 74°C respectively Comparisons were also made between the simulated and experimental data for the solar water heater without and with PCM. Minimum inlet water temperatures of 41.54 and 36°C were observed for the simulated and experimental model while, 42.69 and 74°C were both recorded for outlet temperatures respectively, for solar water heater without PCM. For the solar water heater with PCM, the inlet temperatures for the simulation and experimental model were found to be 42°C and 56°C respectively. A maximum outlet water temperature of 108°C was obtained from the experimental model compared to 45°C obtained from simulation. The temperature of the hot water obtained was remarkable and sufficiently enough for many domestic and industrial applications. Finally, the solar water heating system with phase change materials finds useful application and acts as a renewable energy resource in regions where there is inconsistent or poor sunlight.